Fullerates: Interaction of divalent metal ions with Langmuir monolayers and multilayers of mono-substituted C60-malonic acid - Patel, Harish; Didymus, Jon; Wong, Kim K. W.; Hirsch, Andreas; Skiebe, Andreas; Lamparth, Iris; Mann, Stephen (Chemical Communications, 1996)
Stable Langmuir monolayers of C[C(COH)] are formed on pure water and on solutions containing Ca or Cd ions; cation-headgroup interactions result in expanded monolayers and the transfer of Ca-fullerene multilayers onto quartz substrates.